Editorial (English) - Abar, Celina A. A. Pereira (Revista do Instituto GeoGebra Internacional de São Paulo, 2023)
The third issue of the volume 12, 2023, presents six articles and four proposals for action seeking to encompass the different possibilities and paths with the GeoGebra can be investigated.